Pemanfaatan Smiling West Java Ambassador dalam Promosi Pariwisata melalui Media Sosial - Azril Muhammad Shafa; Sophia Novita (UNISBA Press, 2024)
Abstract. The Smiling West Java Ambassador program, conducted by the West Java Provincial Department of Tourism and Culture, aims to promote tourism in West Java through social media platforms. In the era of modern tourism dynamics or Digital Tourism, community involvement is a key strategy in tourism promotion. This program is an initiative of the West Java Provincial Department of Tourism and Culture that mobilizes community participation in tourism promotion. The research's objective is to explore reasons for community involvement, provided empowerment, content strategies, and methods to overcome challenges in the Smiling West Java Ambassador program. Employing a qualitative method with a case study approach, the research reveals the uniqueness of community engagement in social media promotion trends, utilizing theories of community participation and promotional content to analyze collected data. Data collection involved interviews, observations and documentation. Findings indicate that empowering and involving communities in tourism promotion programs can have positive impacts, enhancing local participation, sustainable tourism, and creating authentic and engaging content, thereby raising awareness of tourism potential in West Java. Furthermore, the West Java Provincial Department of Tourism and Culture effectively overcame challenges through comprehensive strategies such as collaborating with local governments, tourism stakeholders, and active social media users, ensuring program responsiveness to market needs and latest tourism trends. The implications underscore the importance of continued community participation in similar programs in the future, alongside enhancing promotional strategies focusing on local involvement to strengthen regional tourism industries and sustainable tourism. Abstrak. Program Smiling West Java Ambassador, yang dilakukan oleh Dinas Pariwisata dan Kebudayaan Provinsi Jawa Barat, bertujuan untuk mempromosikan pariwisata Jawa Barat melalui media sosial. Di era dinamika pariwisata modern atau Digital Tourism, keterlibatan masyarakat menjadi strategi utama dalam promosi pariwisata. Program ini adalah inisiatif dari Disparbud Jabar yang mengajak partisipasi masyarakat dalam mempromosikan pariwisata. Penelitian ini bertujuan untuk menyelidiki alasan keterlibatan masyarakat, pemberdayaan yang diberikan, strategi konten, dan cara mengatasi hambatan dalam program Smiling West Java Ambassador. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan studi kasus. Penelitian ini menunjukkan keunikan terkait keterlibatan masyarakat dalam tren promosi melalui media sosial dengan menggunakan teori partisipasi masyarakat dan konten promosi. Pengumpulan data dilakukan melalui wawancara, pengamatan dan dokumentasi. Hasil penelitian menunjukkan bahwa dengan memberdayakan dan melibatkan masyarakat, program promosi pariwisata dapat memberikan dampak positif dalam meningkatkan keterlibatan lokal, berkelanjutan pariwisata, dan menciptakan konten yang autentik dan menarik, sehingga meningkatkan kesadaran akan potensi pariwisata di Jawa Barat. Selain itu, Disparbud Jabar berhasil mengatasi hambatan dengan menerapkan strategi kolaboratif, termasuk dengan pemerintah daerah, pelaku pariwisata, dan masyarakat. Implikasi dari penelitian ini menunjukkan pentingnya mendorong partisipasi masyarakat dalam program serupa di masa mendatang, serta meningkatkan strategi promosi yang berfokus pada keterlibatan lokal untuk memperkuat industri pariwisata daerah dan pariwisata berkelanjutan.